Interband and Intersubband Optical Transition Matrix Elements of Ge/Gesisn Quantum Well - W. J., Fan (ENCON 2013, 2013)
The interband and intersubband optical transition matrix elements of a tensile-strained Ge/GeSiSn quantum well are investigated by using an 8-band k·p method. For conduction to valence band interband optical transition, the S→X,Y,Z transitions are dominant. For intersubband optical transition including the conduction to conduction band and the valence to valence band transitions, the S→X,Y,Z transitions and X,Y,Z →S transitions are significant due to the strong interaction between the conduction band and valence band, and the S, X,Y,Z → S,X,Y,Z transitions are greatly depressed, which are completely different with the results of single band effective mass approximation. The results will be helpful to design optoelectronic devices, such as Laser and LED diodes, photodetector, and solar cell.